Synovium Targeting Delivery of TNFα Blocker for Rheumatoid Arthritis Therapy - A Mini Review - Riyona Desvy Pratiwi, Muhammad Novrizal Abdi Sahid (Journal of Applied Pharmaceutical Science, 2018)
Tumor necrosis factor α (TNFα) blockers are proven to be potential suppressing agents for rheumatoid arthritis. Aside from showing significant effects in clinical treatment, they are also known as the top-selling biological agents. However, several systemic side effects related to infection and cancer are shown after treatments with systemic TNFα blockers. In order to reduce and overcome the side effects, a targeted delivery is then requested. Synovium or synovial membrane is considered as a promising delivery target because TNFα is highly accumulated within it. The current article reviews a number of strategies that might be applied in the synovium targeting delivery of TNFα blockers.
Keywords: Rheumatoid arthritis, tumor necrosis factor &alpha; blockers, synovium, targeted delivery.